2021
DOI: 10.5812/aapm.112880
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Adding Dexmedetomidine to Ropivacaine in Pediatric Caudal Epidural Block: A Randomized, Double-blinded Clinical Trial

Abstract: Background: Caudal block is one of the methods of pain management performed following lower abdominal surgery, though having its own limitations. Objectives: In the present study, the effects and side effects of adding dexmedetomidine to ropivacaine in the caudal epidural block were investigated in children after lower abdominal surgery. Methods: In this randomized, double-blinded clinical trial, 46 children aged three to six years were divided into two groups to perform a caudal block following lower abdomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 19 publications
1
33
0
Order By: Relevance
“…The addition of adjuvants to local anesthetics for nerve block prolongation is a common practice in regional anesthesia (5)(6)(7). Many efforts have studied adjuvants that increase the duration of analgesia while simultaneously maintaining a safe side effect profile (8)(9)(10). The most commonly employed agents are perineural dexamethasone and dexmedetomidine (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…The addition of adjuvants to local anesthetics for nerve block prolongation is a common practice in regional anesthesia (5)(6)(7). Many efforts have studied adjuvants that increase the duration of analgesia while simultaneously maintaining a safe side effect profile (8)(9)(10). The most commonly employed agents are perineural dexamethasone and dexmedetomidine (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…A similar study by Imani et al revealed that adding dexmedetomidine to ropivacaine in caudal block anesthesia potentiated the analgesic effect and decreased the analgesic requirements following infraumbilical surgeries in children without causing any side effects ( 16 ). Moreover, Al-Zaben et al compared the efficacy of 2 mcg.kg-1 and 1 mcg.kg-1 of dexmedetomidine when used with bupivacaine for caudal block anesthesia.…”
Section: Discussionmentioning
confidence: 97%
“…Dexmedetomidine is a newer alpha-2 agonist that has an eight-fold higher alpha-2 selectivity than clonidine, with an alpha-2: alpha-1 receptor specificity of 1,600:1 and a safer side effect profile (20,(24)(25)(26). Its sedative, anxiolytic, and analgesic properties suitably position DEX as a nonopioid adjuvant to local anesthetics (27)(28)(29)(30)(31).…”
Section: Dexmedetomidinementioning
confidence: 99%